Recession Potential and Its Impact (A Study of Online Business Sustainability in Indonesia) - Prasetian Dewi, Arlinta (Fakultas Syari'ah Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo., 2023)
Recession turmoil is increasingly being felt in several countries in the world, even Indonesia is not spared from being affected. The thing that will be most affected is economic problems, both macro and micro. This includes the sustainability of online businesses which are increasingly prevalent in Indonesia. This study aims to find out whether online business in Indonesia is still being used effectively amidst the looming recession issue? What are the tips that must be done by online business entrepreneurs so as not to lose money in the future? From the results of the research it is known that even though it is in the shadow of a recession, the e-commerce business will continue to grow because Indonesia is dominated by domestic consumption, so that online business actors need to have tips to be able to survive including: managing cash flow, business actors must be able to choosing fast moving products and cutting costs that don't make a real contribution, apart from that business actors must be very careful in choosing a marketplace that provides many benefits and conveniences for both sellers and buyers.